2019
DOI: 10.1039/c8ta11596f
|View full text |Cite
|
Sign up to set email alerts
|

A metal–organic framework with suitable pore size and dual functionalities for highly efficient post-combustion CO2 capture

Abstract: A novel porous material was realized for highly efficient post-combustion CO2 capture with high CO2 adsorption capacity, high selectivity and moderate heat of adsorption, mainly attributed to the suitable pore size and dual functionalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(98 citation statements)
references
References 68 publications
5
93
0
Order By: Relevance
“…Thus, we want to study MOF which has abundant bases and micropores. Moreover, in recent years, it has been shown that the establishment for the porous MOFs with bifunctional ligands is a feasible way to obtain the donor positions discordant MOFs [20][21][22]. In this research, a novel MOF containing Co(II) ions as nodes f[Co(L)]Á4H 2 OÁ2CH 3 CNg n (1) have been prepared via Co(NO 3 ) 2 Á6H 2 O reacting with the bifunctional ligand 5-(3,5-di-pyridin-4-yl- [1,2,4]triazol-1-ylmethyl)-isophthalic acid (H 2 L) under the solvothermal conditions (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we want to study MOF which has abundant bases and micropores. Moreover, in recent years, it has been shown that the establishment for the porous MOFs with bifunctional ligands is a feasible way to obtain the donor positions discordant MOFs [20][21][22]. In this research, a novel MOF containing Co(II) ions as nodes f[Co(L)]Á4H 2 OÁ2CH 3 CNg n (1) have been prepared via Co(NO 3 ) 2 Á6H 2 O reacting with the bifunctional ligand 5-(3,5-di-pyridin-4-yl- [1,2,4]triazol-1-ylmethyl)-isophthalic acid (H 2 L) under the solvothermal conditions (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…S5). The CO 2 /N 2 (15/85) separation selectivity on ZU-16-Co is up to 690 at 1.0 bar, much higher than that on r1KCHA (80) [18], NKU-521 (40) [39], UTSA-16 (314) [40], Mg-MOF-74 (150) [40], SIFSIX-2-Cu-i (140) [37] and UTSA-120a (600) [41]. Furthermore, CO 2 /CH 4 (50/50) separation selectivity on ZU-16-Co was calculated to be 120, also comparable to the state-of-the-art materials, such as SIFSIX-2-Cu-i (33) [37], SIFSIX-3-Zn (231) [37], 13X (103) [37], Mg-MOF-74 (137) [37], and MOF-505 (27.8) [42].…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to their ease of functionalization using CO 2 -philic functional groups. MIL-140 [41] and UTSA-120a [46] showed one of the highest selectivity of 1900 and ~600 for CO 2 in binary mixtures (CO 2 /N 2 ). Extremely high selectivity of 7531 for CO 2 /N 2 binary mixture was recorded for MOF MFUM-1(Cu) [139] without information on its adsorption capacity.…”
Section: Co 2 Selectivity Of Adsorbents At Preand Post-combustion Conmentioning
confidence: 98%
“…Polymer IHBPA (TEPA) [138] and PI-COF-2 [80] had adsorption capacities of 7.65 mmol/g and 5.8 mmol/g respectively at 1 bar and 298K while AC CuO NP-AC [108], ARG-K-Im [98] and DAC-AC-CO 2 [98] had adsorption capacities of 6.72 mmol/g, 5.63 mmol/g and 5.52 mmol/g respectively at 1 bar and 298K. MOF UTSA-120a [46] was the highest performing MOF in this regard with the adsorption capacity of 5.00 mmol/g at 1 bar and 296K; all other MOFs performed below this value in this study. This may be due to the incorporation of functional tetrazine groups into the structure, which improved its affinity for CO 2.…”
Section: Co 2 Adsorption Capacity At Postcombustion Conditionsmentioning
confidence: 98%